Circular Dichroism as a Rapid Method for Analyzing the Binding of a Targeting Ligand to the Surface of Albumin Nanoparticles - Karolina Kulig; Zuzanna Denisiuk; Małgorzata Kłósek; Aleksandra Owczarzy; Wojciech Rogóż; Łukasz Sędek; Małgorzata Maciążek-Jurczyk (MDPI AG, 2023)
Circular dichroism (CD) is an excellent and rapid method for analysis of chiral molecules, whose mechanism is based on the absorption of left- and right-hand circularly polarized light. Albumin nanoparticles are biocompatible and easy to modify due to their structure. Tumor cell membranes are among the molecules that direct nanoparticles into the tumor microenvironment, but methods to study them except molecular biology are not well validated yet. The aim of this study was to use circular dichroism as the tool to qualitatively assess ligand binding on the surface of nanoparticles. Human serum albumin (HSA) nanoparticles with encapsulated 5-fluorouracil (5-FU) were coated on MCF-7 cell membranes and subjected to CD analysis. This study was completed using sample and separate 5-FU release analysis. The amount of encapsulated drug in nanoparticles affects the binding of cell membranes on the nanoparticle surface. In addition, it can be suspected that the alpha structure of HSA was mainly used for the interaction, which confirms the effectiveness of using CD as a rapid technique for analyzing ligand-nanoparticle interactions. The release of 5-FU from the nanoparticles proceeds in an uncontrolled manner, making this study in need of further modification and investigation.